Inhibición bacteriana del aceite esencial de Salvia Officinalis “Salvia” frente a Staphylococcus Aureus. - Meza Rojas, Yussilin Banesa; Quispe Carhuamaca, Ingrid (Universidad Privada de Huancayo Franklin Roosevelt, 2023)
El objetivo de la siguiente investigación es evaluar la capacidad antibacteriana del aceite esencial de salvia officinalis “salvia” frente a staphylococcus aureus. Como método se utilizó el diseño experimental de corte transversal, la muestra conformada por aceite esencial de salvia y colonias de Staphylococcus aureus. Los resultados muestran los promedios de halos de inhibición, en la concentración al 50% halos de 7,71 mm en la concentración al 75% halos de inhibición de 11,88 mm y en la concentración al 100%, muestra halos de inhibición de 18,79 mm; clindamicina. En conclusión, el aceite esencial de Salvia officinalis, tiene capacidad antibacteriana frente a Staphylococcus aureus, mostrando halos de inhibición con diámetros dependiente a la concentración.

The objective of the following research is to evaluate the antibacterial capacity of salvia officinalis "salvia" essential oil against Staphylococcus aureus. The method used was the cross-sectional experimental design, the sample was composed of salvia essential oil and Staphylococcus aureus colonies. The results show the average inhibition halos, in the 50% concentration halos of 7.71 mm, in the 75% concentration inhibition halos of 11.88 mm and in the 100% concentration, it shows inhibition halos of 18.79 mm; clindamycin. In conclusion, the essential oil of Salvia officinalis has antibacterial capacity against Staphylococcus aureus, showing inhibition halos with diameters dependent on the concentration.
Bacterial inhibition of Salvia Officinalis "Salvia" essential oil against Staphylococcus Aureus.
Keywords: Aceite esencial; Bacteriana; Inhibición; Halos; http://purl.org/pe-repo/ocde/ford#3.01.05